2012
DOI: 10.1016/j.jhydrol.2011.11.051
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous or homogeneous? Implications of simplifying heterogeneous streambeds in models of losing streams

Abstract: KeywordsGroundwater/surface water interaction Streambed heterogeneity Losing streams Disconnection Numerical modeling Inverse modeling s u m m a r y A common approach in modeling surface water-groundwater interaction is to represent the streambed as a homogeneous geological structure with hydraulic properties obtained by means of model calibration. In reality, streambeds are highly heterogeneous, and there are currently no methodical investigations to justify the simplification of this geologic complexity. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 19 publications
2
76
0
Order By: Relevance
“…In particular the concept of GW-SW controlled by head in surface water and groundwater and a stream bed leakage coefficient (see section 2.1) become more challenging to apply as all the parameters involved are known to show large spatial (and temporal) heterogeneity (see, e.g. Fleckenstein et al 2006;Irvine et al 2012).…”
Section: Characteristics Of the Local Scalementioning
confidence: 99%
“…In particular the concept of GW-SW controlled by head in surface water and groundwater and a stream bed leakage coefficient (see section 2.1) become more challenging to apply as all the parameters involved are known to show large spatial (and temporal) heterogeneity (see, e.g. Fleckenstein et al 2006;Irvine et al 2012).…”
Section: Characteristics Of the Local Scalementioning
confidence: 99%
“…Overall, the heterogeneities modify both the penetration depth and the residence time of streamaquifer exchanges (Cardenas et al, 2004;Salehin et al, 2004;Sawyer and Cardenas, 2009). The common hypothesis of an homogeneous bed therefore generates errors on the assessment of stream-aquifer exchanges (Cardenas et al, 2004;Frei et al, 2010;Kalbus et al, 2009;Irvine et al, 2012), which are difficult to estimate for real case studies due to the fact that small scale heterogeneities are difficult to assess.…”
Section: The Stream-aquifer Interface At the Local Scale -The Hyporhementioning
confidence: 99%
“…Between these two states the hydraulic connection is transitional [34]. Irvine et al [35] compared the degree of connection and the water flux between an aquifer and a 20 m by 20 m section of a hypothetical losing river with a heterogeneous streambed, and between an aquifer and the same river with a homogeneous streambed and equivalent water fluxes. They found that the accuracy of the predicted fluxes with the homogeneous streambed model depended on the degree of connection between the river and aquifer at the calibrated state and on whether the water table was rising or falling.…”
Section: Introductionmentioning
confidence: 99%